2021
DOI: 10.3389/fbioe.2021.718753
|View full text |Cite|
|
Sign up to set email alerts
|

Development and Delivery Systems of mRNA Vaccines

Abstract: Since the outbreak of SARS-CoV-2, mRNA vaccine development has undergone a tremendous drive within the pharmaceutical field. In recent years, great progress has been made into mRNA vaccine development, especially in individualized tumor vaccines. mRNA vaccines are a promising approach as the production process is simple, safety profiles are better than those of DNA vaccines, and mRNA-encoded antigens are readily expressed in cells. However, mRNA vaccines also possess some inherent limitations. While side effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
82
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 43 publications
0
82
0
2
Order By: Relevance
“…This is also consolidated by the fact that there is a number of clinical trials of prophylactic DNA vaccines for the prevention of various infectious diseases (NCT04591184, NCT01487876, NCT04445389, NCT01498718, etc.). The technique of developing an mRNA-based vaccine from the beginning to the step of commercialization comprises antigen selection, optimization (addition of immunogenic sequences), plasmid design and synthesis, plasmid transformation into competent bacterial cells, its amplification, extraction, purification, linearization, in vitro transcription of mRNA, purification, capping, packing of mRNA in an effective delivery system, in vitro validation of the antigen expression, in vivo analysis, and ultimately, clinical studies [ 39 , 40 ]. Notably, the DNA vaccine approach also consists of a similar procedure except for the in vitro transcription and other mRNA-related steps meaning that the manufacturing is simpler and time-saving [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is also consolidated by the fact that there is a number of clinical trials of prophylactic DNA vaccines for the prevention of various infectious diseases (NCT04591184, NCT01487876, NCT04445389, NCT01498718, etc.). The technique of developing an mRNA-based vaccine from the beginning to the step of commercialization comprises antigen selection, optimization (addition of immunogenic sequences), plasmid design and synthesis, plasmid transformation into competent bacterial cells, its amplification, extraction, purification, linearization, in vitro transcription of mRNA, purification, capping, packing of mRNA in an effective delivery system, in vitro validation of the antigen expression, in vivo analysis, and ultimately, clinical studies [ 39 , 40 ]. Notably, the DNA vaccine approach also consists of a similar procedure except for the in vitro transcription and other mRNA-related steps meaning that the manufacturing is simpler and time-saving [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The classical problems involving the creation of mRNA vaccines include mRNA stability and delivery systems. It remains to be seen whether mRNA vaccines might have a utility for HSV; however, initial studies with the trivalent vaccine have been promising, showing increased efficacy compared to a subunit formulation ( Liu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mRNA is encapsulated in the aqueous core of the liposomes to protect it from RNase [ 100 ]. Mostly, lipids are screened by pH-responsive materials because the cationic lipids are easily captured by immune cells [ 101 ]. Norbert et al reported that mRNA encapsulated in lipid nanoparticles can induce high levels of TFH cells and GCB, generate effective neutralizing antibody response and antigen-specific CD4+ T cell response [ 102 ].…”
Section: Nanoparticles For Inhaled Vaccinesmentioning
confidence: 99%
“…Norbert et al reported that mRNA encapsulated in lipid nanoparticles can induce high levels of TFH cells and GCB, generate effective neutralizing antibody response and antigen-specific CD4+ T cell response [ 102 ]. Polylysine was the first cationic polymer used successfully to deliver plasmid DNA in 1987 [ 101 ]. Since then, other polymers have been used for that purpose such as spermine, chitosan, polyethyleneimine, polyurethane, poly-amido-amine (PAA), polyethylenimine (PEI) and poly-beta amino-esters (PBAEs).…”
Section: Nanoparticles For Inhaled Vaccinesmentioning
confidence: 99%